IDENTIFIKASI KETERLAMBATAN SISWA DALAM MENUNTASKAN TARGET HAFALAN JUZ 30 DI MADRASAH IBTIDAIYAH - Andryadi, Andryadi; Misdarwati; Yanti Isdahlia; Hasmiyati; Azzah Aqila (Abtadi : Jurnal Pendidikan Dasar, 2025)
The delay of students in completing the memorization of Juz 30 is something thatshould be considered, because it can potentially hinder the continuation of the student's memorization process and reduce the level of enthusiasm of students to continue the memorization caused by it. This study aims to determine what factors cause the delay, especially in the tahfidz class of Madrasah Ibtidaiyah Raudhatul Ma'arif. With a qualitative approach and case study method, data were obtained through interviews and direct observation. The results of the study showed that obstacles came from two sides, namely from within the students themselves and from their surroundings. From the internal side, students tend to be less consistent in repeating memorization, are not yet fluent in reading the Qur'an, and some are too ambitious to add to their memorization without strengthening what has beenmemorized. From the external side, lack of support from home, an unsupportive learning environment, peer influence, and excessive use of gadgets also slow down the memorization process. By understanding these various obstacles, it is hoped that all parties, both teachers, parents, and students themselves can be more sensitive and work together so that memorization of the Qur'an can run smoothly and enjoyably.